A multidimensional data model design for building energy management. Issue 4 (October 2016) - Cavalheiro, José; Carreira, Paulo
Abstract: Data organization is a critical aspect in Building Energy Data Management. Yet, despite the importance of the topic, no sound reference model for energy data has been proposed in the literature that has been developed according to well-founded methodologies. This article proposes a reference data model developed according to standard multidimensional modeling methodologies and improved iteratively in review meetings with expert users (in the building energy management domain). The quality of the model is evaluated according to complexity, usability, and design metrics thus achieving a high-quality re-usable multidimensional data model that can be applied to create or improve on the data model designs of building energy management systems.